СТРУКТУРНЫЕ ДИСПРОПОРЦИИ КАК УГРОЗА ЭКОНОМИЧЕСКОЙ БЕЗОПАСНОСТИ РОССИИ - N. V. Osokina; E. V. Slesarenko (Russian Journal of Economics and Law)
Objective: to determine the impact of structural disproportions on the level of economic security of the national economy. Methods: comparison, generalization, observation, systemic analysis, data grouping, theoretical cognition, the method of analogy and historical method. Results: basing on the analysis of scientific economic literature and statistical data, the historical background is revealed of the emergence of structural disproportions in the Russian economy, the origins of which had been laid long before the formation of the USSR and tended to strengthen during the Soviet period, and later during the period of transformation processes that swept the country at the turn of XX-XXI centuries; the influence of structural disproportions on the security of the Russian economy was described, which can be interpreted as a threat, characterized by a complete de-industrialization of the economy, reduction of innovation development, degradation of economic base and scientific potential, increasing dependence on vital consumer and industrial goods; there is a need to change the vector of socio-economic development of Russia and form a new model of structural modernization. Scientific novelty: for the first time on the basis of the presented methods, the article studies the impact of structural disproportions on the level of economic security of the national economy. Practical significance: the main provisions and conclusions of the article can be used in scientific and teaching activities in addressing issues of economic security of the national economy.